2012
DOI: 10.1021/ol300377a
|View full text |Cite
|
Sign up to set email alerts
|

Diastereoselective Additions of Allylmetal Reagents to Free and Protected syn-α,β-Dihydroxyketones Enable Efficient Synthetic Routes to Methyl Trioxacarcinoside A

Abstract: Two routes to the 2,6-dideoxysugar methyl trioxacarcinoside A are described. Each was enabled by an apparent α-chelation-controlled addition of an allylmetal reagent to a ketone substrate containing a free α-hydroxyl group and a β-hydroxyl substituent, either free or protected as the corresponding di-tert-butylmethyl silyl ether. Both routes provide practical access to gram-quantities of trioxacarcinose A in a form suitable for glycosidic coupling reactions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
12
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 40 publications
1
12
0
Order By: Relevance
“…High regioselectivity and diastereoselectivity, however, were observed in the addition to 23e through the γ-addition pathway. This addition could proceed either through ketone 23e or the corresponding magnesium alkoxide, considering that the rate of addition of allylic Grignard reagents to carbonyl compounds is comparable to the rate of proton transfer. , A control experiment indicated that addition to the magnesium alkoxide is consistent with the selectivity shown in Table . One equivalent of methylmagnesium chloride was first added to 23e at −78 °C to deprotonate the hydroxyl group, then prenylmagnesium chloride was added to the mixture.…”
Section: Resultsmentioning
confidence: 89%
“…High regioselectivity and diastereoselectivity, however, were observed in the addition to 23e through the γ-addition pathway. This addition could proceed either through ketone 23e or the corresponding magnesium alkoxide, considering that the rate of addition of allylic Grignard reagents to carbonyl compounds is comparable to the rate of proton transfer. , A control experiment indicated that addition to the magnesium alkoxide is consistent with the selectivity shown in Table . One equivalent of methylmagnesium chloride was first added to 23e at −78 °C to deprotonate the hydroxyl group, then prenylmagnesium chloride was added to the mixture.…”
Section: Resultsmentioning
confidence: 89%
“…The low selectivity exhibited in reactions of allylmagnesium halides with chiral, α-alkoxy ketones is evident when direct comparisons to other organomagnesium reagents are made . For example, we found that whereas addition of n -propylmagnesium chloride to ketone 2 was highly selective for the chelation-control product (eq ), addition of allylmagnesium chloride proceeded with low stereoselectivity, favoring the opposite stereoisomer (eq 2).…”
mentioning
confidence: 82%
“… 12 We elected to explore initial couplings with 1- O -acetyl trioxacarcinose A ( 3 , Figure 2 ), which is available in multi-gram amounts by a short and practical sequence. 13 We found that when a mixture of diol 2 (1 equiv), glycosyl donor 3 (2 equiv, a 1:12 mixture of α- and β-anomers, respectively), and powdered 4-Å molecular sieves in dichloromethane at −40 °C was treated with boron trifluoride etherate (1.0 equiv) as promoter the α-monoglycoside 4 was formed in 79% yield (23 mg). The β-configured glycosylation product was not observed.…”
Section: Resultsmentioning
confidence: 95%